A 53-µA-Quiescent 400-mA Load Demultiplexer Based CMOS Multi-Voltage Domain Low Dropout Regulator for RF Energy Harvester. - Poongan, Balamahesn; Rajendran, Jagadheswaran; Yizhi, Li; Mariappan, Selvakumar; Parameswaran, Pharveen; Kumar, Narendra; Othman, Masuri; Nathan, Arokia (MDPI AG, 2023)
A low-power capacitorless demultiplexer-based multi-voltage domain low-dropout regulator (MVD-LDO) with 180 nm CMOS technology is proposed in this work. The MVD-LDO has a 1.5 V supply voltage headroom and regulates an output from four voltage domains ranging from 0.8 V to 1.4 V, with a high current efficiency of 99.98% with quiescent current of 53 µA with the aid of an integrated low-power demultiplexer controller which consumes only 68.85 pW. The fabricated chip has an area of 0.149 mm2 and can deliver up to 400 mA of current. The MVD-LDO's line and load regulations are 1.85 mV/V and 0.0003 mV/mA for the low-output voltage domain and 3.53 mV/V and 0.079 mV/mA for the high-output voltage domain. The LDO consumes only 174.5 µW in standby mode, making it suitable for integrating with an RF energy harvester chip to power sensor nodes.
Peer reviewed: True
Keywords: bandgap voltage reference; demultiplexer; feedback network; internet of things; multi-voltage domain low dropout; power management unit; radio frequency energy harvester; system on chip